Informative value of the use of infrared thermography in the complex diagnosis of postpartum dysgalactia syndrome in sows - Latynina Evgeniya Sergeevna; Dyulger Georgy Petrovich; Leontiev Leonid Borisovich (BIO Web of Conferences, 2021)
The article presents scientific materials on the use of the method of remote infrared thermography in the complex diagnosis of postpartum dysgalactia syndrome in sows. The general body temperature and the temperature of the skin surface of individual parts of its body are important indicators of the functional state of the animal body. In veterinary practice, they are widely used for the diagnosis and differential diagnosis of various diseases. Now, the most perfect way to register the spatial distribution of temperatures is the method of infrared thermography. Infrared thermography is the process of obtaining a visible image of an object based on its infrared radiation, which is low-energy and invisible to the human eye. Infrared radiation from the skin depends on both external and internal factors. Their change will undoubtedly affect the thermal conductivity of the body and reflect itself on thermograms in the form of thermal patterns of various color grading. Despite the abundance of factors affecting skin radiation, infrared thermography is a promising method for the timely diagnosis of many diseases. The undoubted advantages of this method are its non-invasiveness, the absence of contraindications and species-specificity, and the non-invasiveness of the examination. In this connection, the purpose of this study was to determine the information content of the use of infrared thermography in the complex diagnosis of postpartum dysgalactia syndrome in sows.